Hubungan Kepemimpinan Ketua Kelompok Tani dengan Efektivitas Kelompok Tani di Desa Waiheru Kecamatan Baguala Kota Ambon - Kostan Popana; Meilvis E. Tahitu; Jeter D. Siwalette (COMSERVA : Jurnal Penelitian dan Pengabdian Masyarakat, 2023)
The research's purposes are to analyze the leadership role of farmer group leaders, analyze the effectiveness of farmer groups, and analyze the correlation between the leadership roles of farmer group leaders and group efficacy. In the Baguala District's Waiheru Village, this study was carried out. 42 persons made up the sample for this study utilizing a simple random sampling technique. Primary data came from interviews with respondents, while secondary data came from literature reviews and materials pertaining to research issues. The Spearman Rank correlation coefficient test is then used to analyze the given data. The results showed that the leader of the Waiheru farmer group in carrying out his role as a leader in increasing group cohesiveness, increasing group cooperation, his role in increasing member motivation and decision making was classified as good, while the role of solving problems and reconciling conflicts was classified as moderate. The effectiveness of farmer groups is strongly and unidirectionally correlated with the leadership role of group leaders.